2009
DOI: 10.1038/oby.2008.461
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Combination Medication for the Treatment of Obesity

Abstract: Existing obesity therapies are limited by safety concerns and modest efficacy reflecting a weight loss plateau. Here, we explore combination therapy with bupropion (BUP), a putative stimulator of melanocortin pathways, and an opioid antagonist, naltrexone (NAL), to antagonize an inhibitory feedback loop that limits sustained weight reduction. In vitro electrophysiologic experiments were conducted to determine the extent to which BUP+NAL stimulated hypothalamic pro‐opiomelanocortin (POMC) neurons in mouse brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
204
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(221 citation statements)
references
References 44 publications
5
204
0
6
Order By: Relevance
“…Animal models show that the expression of POMC-mRNA is regulated by dopamine, especially the activation of D2-receptors of the ARH [Tong and Pelletier, 1992]. Bupropion appears to increase the activity of hypothalamic POMCproducing cells [Greenway et al 2008[Greenway et al , 2009. Previous studies have shown that methylphenidate can amplify dopaminergic signalling within the mesolimbic circuitry when humans are exposed to food stimuli [Volkow et al 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models show that the expression of POMC-mRNA is regulated by dopamine, especially the activation of D2-receptors of the ARH [Tong and Pelletier, 1992]. Bupropion appears to increase the activity of hypothalamic POMCproducing cells [Greenway et al 2008[Greenway et al , 2009. Previous studies have shown that methylphenidate can amplify dopaminergic signalling within the mesolimbic circuitry when humans are exposed to food stimuli [Volkow et al 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Em contrapartida, foi demonstrado que a β-endorfina, um opioide endóge-no, é responsável por um mecanismo de autoinibição da via da POMC, resultando em um aumento da ingestão alimentar em roedores. Ao inibir os receptores opioides, a naltrexona libera os neurônios da POMC da inibição pela β-endorfina e, portanto, potencializa os efeitos ativadores dessa via pela bupropiona (26,27). Adicionalmente, alguns estudos em ratos demonstraram que a ingestão de alimentos palatáveis (por exemplo, doces) leva a aumento dos níveis de β-endorfina no hipotálamo.…”
Section: Bupropiona/naltrexonaunclassified
“…Naltrexone blocks β-endorphin and increases the release of α-MSH, which can continue to inhibit feeding. 42 In a 24-week dose-ranging study, 419 subjects were randomized but only 244 (64%) completed the trial. Among the completers, weight loss was 1.2 kg in the placebo group, 3.1 kg in the bupropion-treated group, but only 1.6 kg with the highest (48 mg/day) dose of naltrexone.…”
Section: Topiramate and Phenterminementioning
confidence: 99%